Weight Considerations in Pharmacotherapy for Type 2 Diabetes - Vicky Cheng; Sangeeta R. Kashyap (Journal of Obesity)
Obesity has been increasing in prevalence worldwide and the majority of patients with type 2 diabetes are either overweight or obese. Diabetes management in this population has been difficult since a number of antidiabetes agents are associated with weight gain. The effects of various antidiabetes agents and antiobesity agents on glycemic control and body weight will be reviewed. Briefly, sulfonylureas, thiazolidinediones, and insulin are associated with weight gain, whereas metformin and amylin analogs are weight neutral or associated with modest weight loss. Dipeptidyl-peptidase-4 inhibitors are weight neutral, whereas glucagon-like peptide-1 analogs are associated with weight loss. The effect of orlistat and sibutramine in type 2 diabetes is also evaluated. The treatment of diabetes should not only focus on glycemic control as its sole intention, but it should factor in the effect of these various agents on weight, as well, since obesity aggravates insulin resistance, beta cell failure, and cardiovascular risk.